Analysis of the movie "Rampage: Devastation" from the perspective of Public Health and the One Health approach (Mayéutica Revista Científica de Humanidades y Artes, 2025)
A personal instrumental analysis of the film “Rampage: Devastation” is presented, reflecting on it as an instrument for ideological communication by considering it as a symptomatic element of processes of a social nature, with the possibility of also using its professional nature analysis, by giving it a public health approach under the vision of the One Health paradigm.
Keywords: Instrumental Analysis; film; social process; public health; One Health.